Quality of life in patients with mild cognitive impairment - Bárrios, Helena (2013)
Background: Quality of life (QoL) is affected in patients with dementia, but it is not clear whether it is already disturbed in more initial phases of cognitive decline, like Mild Cognitive Impairment (MCI). Aim: Compare the QoL in MCI patients with controls without cognitive impairment, and ascertain whether there are differences in the reports of QoL made by the subjects and by their informants. Methods: Two hundred participants were enrolled, divided into MCI patients (n¼50), MCI informants (n¼50), recruited from a memory clinic and a dementia outpatient clinic, and controls (n¼50) and controls informants (n¼50), recruited in a family practice clinic. QoL was assessed with the QoL in Alzheimer disease (QOL-AD) scale. Results: The total scores of the QOL-AD questionnaire were 32.1 6.9 for MCI patients self-report, 27.2 6.7 for MCI patients in the opinion of their informants, 35.3 4.9 for controls self-report and 35.6 4.9 for controls in the opinion of their informants. MCI patients had lower QOL-AD scores than controls. The QoL reported by patients with MCI was more favorable than the opinion of their informants. Conclusion: The QoL is affected at early stages of cognitive decline. The QoL reported by patients with MCI is better than the opinion of their informants, similarly to what is known in Alzheimer’s disease patients. QoL appears to be an important domain to be evaluated in aging studies.